Approximation Characteristics of Spaces $S_φ ^p$ - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We introduce linear vector spaces $S_φ ^p$ and study their approximation properties. By using the general results obtained, we establish statements concerning the approximation of classes of periodic functions of many variables by trigonometric polynomials.